Indigenous Human Resource Management Practices in Africa: Empirical Lessons from Four Sub-regions - Kiiza, Mark; Basheka, Benon C. (Emerald Publishing Limited., 2018)
Over decades, indigenous management practices and their values in Africa have changed from time to time. However, it continued to remain relevant in most business organisations in developing countries. Today in Africa and across the globe, there is a paradigm shift and stiff competition in human resource management practices as a basic element for effective and efficient business organisations’ performance. Effective human resource management practices and performance of organisations rely on the integration of indigenous management practices and sound strategies aligned to cultural values and cores business objectives. The study covers four regions of Africa as a continent. Empirical teachings of the study form a basis for active reforms and innovations, so as to revamp the use of indigenous knowledge, which was deliberately destroyed by colonial masters. Over the years, human resource management practice has evolved in favour of Western strategies and ideologies. Advocates for curriculum reforms in all African countries so as to incorporate indigenous knowledge content, since it is believed to be the future of Africa. An appropriate employees management practice in Africa is a necessary move in today’s business community as it enhances service delivery and performance. The application of indigenous management practices is believed to play a vital role and invokes effective decision-making practices in the business organisation. Therefore, the chapter traces the origin of indigenous wisdom and its fundamental structure in management practices. This chapter attempts to throw light on indigenous management practices and their values in business organisations in Africa.
Keywords: Indigenous; knowledge; African; management; practices; educators